Effects of die geometry on variation of the deformation rate in equal channel angular pressing - Han, J.-H.; Chang, H.-J.; Jee, K.-K.; Oh, K.H. (KOREAN INST METALS MATERIALS, 2009)
The deformation behavior within the deformation zone of a workpiece during equal channel angular pressing (ECAP) was investigated using the finite element method. The effects of die geometry on the variations of normal and shear deformations were studied with a deformation rate tensor (D). The zero dilatation line, at which the normal components (D11 and D 22) of the deformation rate tensor (D) are zero, in the die coincided with the line of intersection of the two die channels irrespective of die geometry such as curvature angle (χ) and oblique angle (φ), while the maximum shear line, at which the shear components (D12 and D 21) of the deformation rate tensor (D) have maximum value, is dependant on the die geometry. ？ KIM and Springe.